No functional contribution of the gustatory receptor, Gr64b, co-expressed in olfactory sensory neurons of Drosophila melanogaster - Mahadevan, Venkatesh Pal; Lavista-Llanos, Sofía; Knaden, Markus; Hansson, Bill S. (Frontiers in Ecology and Evolution, 2022)
Chemosensation is essential for the survival of insects. Activities like searching for food, mating, and oviposition in the fruit fly, Drosophila melanogaster are to a great extent governed by chemical cues detected via olfaction and gustation. This chemical information is conveyed to higher brain centres via populations of diverse olfactory sensory neurons (OSNs) and gustatory sensory neurons (GSNs) expressing olfactory receptors (ORs) and gustatory receptors (GRs), respectively. ORs are exclusively expressed in the antenna and in the maxillary palps, while GRs are widely expressed in the labellum, tarsi, genitalia etc. Interestingly, 14 GRs were previously reported to be expressed in the antenna of D. melanogaster. However, the spatial expression pattern for all GRs and their functional role are still unclear. Recent data challenge the dogma that single OSNs express a single OR. In the present study, we studied the expression of 12 previously reported GRs among sensory structures on the fly antenna using the Gal4-UAS binary expression system. We observed antennal expression of nine out of the 12 reported. Out of these nine, consistent expression was only apparent for Gr64b, and we reconfirmed its presence in OSNs innervating three glomeruli in the antennal lobe. These glomeruli are known to be innervated by ab5A, ab5B and ab8A OSNs, respectively. Next, we generated double labelling crosses with Gr64b and observed co-expression of Gr64b with Or47a, which is expressed in the ab5B neuron. To elucidate the functional role of Gr64b co-expressed with Or47b, we challenged Or47a-expressing OSNs in wild type and Gr64b-/- mutant flies with odor stimulation using the single sensillum recording technique in two satiation states (fed and starved). Notably, we did not observe any significant odor sensitivity or specificity changes in Gr64b mutants as compared to wild type flies. Taken together, our results reveal co-expression of GRs with ORs in olfactory sensory neurons, while the functional contribution of the GR in this context remains obscure.